Short circuit current limitation using series reactors in 20 kV distribution feeder - Ramdhan Halid Siregar; Alwan Farras; S Syahrizal (Journal Geuthee of Engineering and Energy, 2026)
Short-circuit faults in power distribution systems generate excessive fault currents that can damage electrical equipment and reduce system reliability. One practical method for limiting fault current is the installation of a series reactor or current limiting reactor (CLR). This study analyzes short-circuit current characteristics in the 20 kV Ulee Kareng distribution feeder in Banda Aceh and evaluates the effectiveness of a series reactor in reducing fault current levels. The analysis was performed using ETAP 19.0.1 simulation software based on the IEC 60909 standard. Four fault types were investigated: three-phase, single line-to-ground, line-to-line, and double line-to-ground faults. The simulation results show that the maximum three-phase short-circuit current before reactor installation was 4.066 kA at bus LBU 01-00, while the minimum value was 2.732 kA at bus LBU 42-00. A series reactor with a reactance value of 3.12 Ω was designed to achieve approximately 50% current reduction. After installation, the three-phase short-circuit current at bus LBU 01-00 decreased to 2.103 kA, corresponding to a 48% reduction. The results confirm that the series reactor effectively reduces fault current levels and improves protection system performance without replacing existing circuit breakers. The novelty of this study lies in the evaluation of series reactor performance for all fault types in the actual 20 kV Ulee Kareng distribution feeder using IEC 60909-based ETAP simulations under real operating conditions